POLA-POLA STRATEGI PEMERTAHANAN BAHASA BANJAR DI DESA SANGKING BARU KECAMATAN KELUMPANG SELATAN KABUPATEN KOTABARU - Razali Rahman (STKIP Paris Barantai, 2020)
Strategy Patterns for the Maintenance of Banjar Language in Sangking Baru Village, Kelumpang Selatan Subdistrict, Kotabaru Regency. This research aims to describe the form of strategic patterns in the maintenance of the Banjar language, the form of internal factors that influence the strategic patterns in Banjar language defense, and the form of factors. External factors that influence the strategy patterns in the Banjar language defense. The method used is descriptive method. The results of this study are that there are 9 forms of strategy patterns in Banjar language defense, 5 forms of internal factors that influence strategic patterns in Banjar language defense, and 2 forms of external factors that influence strategy patterns in Banjar language defense. Keywords: Patterns, Understanding Banjar Language, Sangking Baru